Legal status and voluntary abortions by immigrants - Luca Pieroni; Melcior Rosselló Roig; Luca Salmasi; Gilberto Turati (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
We estimate the effect of granting legal status to immigrant women on voluntary abortions. We exploit the 2007 EU enlargement as an exogenous shock to legal status for Romanian and Bulgarian women, considering Italy as a destination country. Using a standard Difference-in-Differences model, we estimate a decline between 60% and 70% in voluntary pregnancy termination (VPT) rates for the new EU citizens from the two Eastern countries. We also introduce a novel framework to separate the total effect of the enlargement into a "citizenship" effect due to (legal or illegal) migrants already present in Italy and a "selection" effect due to new flows of immigrants. We show that the findings are robust to several alternative explanations. The drop in abortions points to legal status as a way to empower immigrant women.
Keywords: F22; K37; I12; J13; 330; Immigration; Abortions; Legal status; EU Enlargement